Endothelial function is unaffected by changing between carvedilol and metoprolol in patients with heart failure-a randomized study - Køber Lars (Cardiovascular Diabetology, 2011)
Abstract Background Carvedilol has been shown to be superior to metoprolol tartrate to improve clinical outcomes in patients with heart failure (HF), yet the mechanisms responsible for these differences remain unclear. We examined if there were differences in endothelial function, insulin stimulated endothelial function, 24 hour ambulatory blood pressure and heart rate during treatment with carvedilol, metoprolol tartrate and metoprolol succinate in patients with HF. Methods Twenty-seven patients with mild HF, all initially treated with carvedilol, were randomized to a two-month treatment with carvedilol, metoprolol tartrate or metoprolol succinate. Venous occlusion plethysmography, 24-hour blood pressure and heart rate measurements were done before and after a two-month treatment period. Results Endothelium-dependent vasodilatation was not affected by changing from carvedilol to either metoprolol tartrate or metoprolol succinate. The relative forearm blood flow at the highest dose of serotonin was 2.42 ± 0.33 in the carvedilol group at baseline and 2.14 ± 0.24 after two months continuation of carvedilol (P = 0.34); 2.57 ± 0.33 before metoprolol tartrate treatment and 2.42 ± 0.55 after treatment (p = 0.74) and in the metoprolol succinate group 1.82 ± 0.29 and 2.10 ± 0.37 before and after treatment, respectively (p = 0.27). Diurnal blood pressures as well as heart rate were also unchanged by changing from carvedilol to metoprolol tartrate or metoprolol succinate. Conclusion Endothelial function remained unchanged when switching the beta blocker treatment from carvedilol to either metoprolol tartrate or metoprolol succinate in this study, where blood pressure and heart rate also remained unchanged in patients with mild HF. Trial registration Current Controlled Trials NCT00497003